Microbiological Analysis of Drinking Water from Different Areas of Lahore - Khan, Imran; Mohsin, Saima (International Journal of Economic and Environmental Geology, 2023)
Access to safe drinking water and its regular monitoring is essential to ensure the health and safety of the public. This study aimed to analyze the microbiological quality of drinking water supplies (filtered and unfiltered) from various towns of Lahore, Pakistan. In total, 135 water samples, with and without filtration (n=90) and additional 45 bottled drinking water samples of different brands from the local market were collected from 9 towns of Lahore. To determine the microbiological quality, all samples were subjected to total plate count, total coliform, E. coli, Streptococci and Salmonella detection. According to the findings, the total plate count from various water supplies was significantly higher as compared to bottled drinking water samples. Drinking water from supplies with filtration and without filtration was found to be contaminated with total coliform (51%), E. coli (51%) and total coliform (84.5%), E. coli (84.5%), faecal Streptococci (15.5%), and Salmonella (11.1%) respectively. In total, 22 (49%) of the filtered and 7 (15.5%) of the unfiltered water samples were found to be microbiologically safe for drinking, whereas 41 (91.1%) bottled drinking water samples met the WHO criteria. To summarize, bottled drinking water is safer than both filtered and unfiltered drinking water. However, all bottled water should not be assumed to be safe for use. The microbial contamination in drinking water supplies, as well as bottled water samples, insinuates for strict monitoring of drinking water by regulatory authorities, and immediate action is required to avoid public health hazards.